prove that , cotx cot2x - cot2x cot3x - cot 3x cot x = 1
Answers
Answered by
9
we know that
tan 3x tan2x tan X = tan 3x -tan 2x-tanx
dividing both sides by tan3x tan2x tan X
tan 3x tan 2x tan X / tan 3x tan 2x tan X = tan3x- tan2x - tanx / tan3x tan2x tanx
1 = 1/tan2x tanx - 1/ tan3x tan c- 1/ tan 3x tan 2x
1 = cotx cot 2x - cot3x cot x - cot3x cot2x
hence proved
Answered by
24
✶⊶⊷⊶⊷⊷⊶⊷ ❍⊷⊶⊷⊶⊷⊶⊷✶
Step-by-step explanation:
tan 3x tan2x tan X = tan 3x -tan 2x-tanx
dividing the both sides by tan3x tan2x tan X
We get
tan 3x tan 2x tan X / tan 3x tan 2x tan X = tan3x- tan2x - tanx / tan3x tan2x tanx
1 = 1/tan2x tanx - 1/ tan3x tan c- 1/ tan 3x tan 2x
SOLVING
1 = cotx cot 2x - cot3x cot x - cot3x cot2x
✶⊶⊷⊶⊷⊷⊶⊷ ❍⊷⊶⊷⊶⊷⊶⊷✶
.
Similar questions